INHIBITION OF THE EFFECTS OF ANGIOTENSIN II ON ADRENAL STEROID PRODUCTION BY DIETARY SODIUM - Davis, Warren W. (1969)
The pressor octapeptide, angiotensin II, can stimulate the production of aldosterone by the adrenal cortex. The present results show that in the dog a high-sodium diet can eliminate the steroidogenic action of angiotensin II, which is thus dissociated from the pressor action which remains. Angiotensin II was infused intravenously for 48 hours into conscious, undisturbed hypophysectomized dogs that were receiving each day either 60 or 200 mEq of dietary sodium. Blood pressure and secretion of aldosterone, corticosterone, and cortisol were measured (1) throughout the infusion in some dogs, and (2) at the end of the infusion in all dogs. In those dogs receiving 60 mEq of sodium, angiotensin II elevated the blood pressure and produced sustained increases of secretion of aldosterone, corticosterone, and cortisol. In those dogs receiving 200 mEq of sodium, angiotensin II, while retaining its pressor activity, had no effect on the production of aldosterone, corticosterone, or cortisol after 24 hours. Thus, if angiotensin II can produce hypertension clinically, there need not be secondary aldosteronism as well.